CD28 Deficiency Ameliorates Blast Exposure-Induced Lung Inflammation, Oxidative Stress, Apoptosis, and T Cell Accumulation in the Lungs via the PI3K/Akt/FoxO1 Signaling Pathway. (2nd September 2019) - Liu, Yunen; Tong, Changci; Xu, Ying; Cong, Peifang; Liu, Ying; Shi, Lin; Shi, Xiuyun; Zhao, Yan; Bi, Guangyuan; Jin, Hongxu; Hou, Mingxiao
Abstract : Although CD28 is associated with the expression of inflammatory mediators, apoptosis-related protein, immunosuppression, and tumorigenesis, the effects of CD28 deficiency on blast exposure-induced lung injury have not been investigated. In this study, we have explored the effects of CD28 on blast exposure-induced lung injury and studied its potential molecular mechanisms. A mouse model of blast exposure-induced acute lung injury was established. Sixty C57BL/6 wild-type (WT) and CD28 knockout (CD28 -/- ) mice were randomly divided into control or model groups. Lung tissue samples were collected 24 h and 48 h after blast injury. Histopathological changes and the expressions of inflammatory-related proteins were detected by hematoxylin-eosin, immunohistochemistry, and immunofluorescence staining. Apoptosis and oxidative stress were evaluated by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining and reactive oxygen species (ROS). Inflammation, apoptosis, oxidative stress, and related pathway protein expression were studied by western blotting. In addition, the levels of CD3 and CD28 proteins were measured by flow cytometry. In the current study, we found that CD28 deficiency significantly inhibited blast exposure-induced increases in the lung weight/body weight ratio and wet weight/dry weight ratio; decreased the infiltration of CD44 + leukocytes, CD163 + macrophages, and CD3 + T cells into the lungs; reduced the expressions of proinflammatory cytokines including IL-1 β, TNF- α, and IL-6; and markedly increased IL-10 expression. CD28 deficiency also significantly attenuated blast exposure-induced ROS, MDA5, and IRE α expressions; increased SOD-1 expression; lowered the number of apoptotic cells and Bax, Caspase-3, and active Caspase-8 expressions; and increased Bcl-2 expression. Additionally, CD28 deficiency significantly ameliorated blast exposure-induced increases of p-PI3K and p-Akt and ameliorated the decrease in the p-FoxO1 expression. Our results suggest that CD28 deficiency has a protective effect on blast exposure-induced lung injury, which might be associated with the PI3K/Akt/FoxO1 signaling pathway.